Morphological characteristics of the skull of Malayan tapir (Tapirus indicus) - Marzuki, Nur Asyiqin Firdaus; Nurhidayat, Nurhidayat; Cahyadi, Danang Dwi; Supratikno, Supratikno; Nisa', Chairun; Agungpriyono, Srihadi; Novelina, Savitri (Journal of Wildlife and Conservation Medicine, 2025)
Background The Malayan tapir (Tapirus indicus) is a notable herbivorous mammal found in Southeast Asia, recognized for its distinctive proboscis and coloration, along with its vital ecological role. According to the IUCN, this species is classified as a threatened species.Objective This study aimed to investigate the morphology of the skull of Malayan tapir, which is associated with feeding behavior.Methods This study employed a descriptive method, comparing a skull specimen of a Malayan tapir to those of horses (Equus sp.). References regarding skull morphology and behavioral video of Brazilian tapirs (T. terrestris) were used for additional comparisons.Results Tapir had a relatively rounder-shaped skull, shorter and thicker os nasale, deeper fossa masseterica, and wider apertura cavum nasi than the horse. The tapir skull specimen displayed an open eye socket, whereas the horse skull displayed a closed eye socket. Morphological observations of the tapir’s behavioral videos showed that tapirs exhibited orthal masticatory movement, driven by brachydont teeth with bilophodont characteristics, which were very different from horses’ hypsodont teeth, designed for lateral movement. The proboscis of the tapir is unique and has a more muscular structure than that of horses, including the nasal bones, which are shorter and thicker.Conclusion These morphological differences influenced the feeding behavior and nocturnal activity of tapir species. This study contributes to broader conservation efforts aimed at conserving tapir populations and their habitats.